Hubungan Ketepatan Teknik Penggunaan Inhaler Dengan Hasil Uji Spirometri Pada Pasien Asma Di Klinik Harum Melati Dan RSU Wisma Rini Kabupaten Pringsewu - Retno Ariza; Fransisca Sinaga; Jordy Oktobiannobel; Siti Fatima Az Zahra (CV. Jasa Sukses Abadi, 2022)
Asthma is a heterogeneous disease with chronic airway inflammation that still be a concern in the world. GINA 2021 explain that if asthma patients are not continuously controlled, it is necessary to review common problems that frequently found, one of which is the wrong inhaler technique. The incorrect of inhaler techniques will have an effect on drug delivery to the lungs which affects the success of therapy and improvement of lung function. To determine the relationship between the accuracy of inhalers technique with the results of the spirometry test in asthmatic patients.This study used a quantitative research with an analytical survey method and a cross-sectional study approach. The study was conducted by observation to see the correlation between the accuracy of the inhaler technique and the results of the spirometry test with parameters FEV1. Sampling was carried out at the Harum Melati Clinic and Wisma Rini Hospital, Pringsewu. There were 173 asthma patients that using inhaler, but only 103 samples met the inclusion criteria, namely patients aged >5 years who used inhalers and taken spirometry examinations. In this study, the inhaler accuracy test was carried out using a checklist 2 times where the first was carried out before education of inhalers technique and the second was carried out after education. Spearmen correlation test showed that there was no relationship between inhaler technique and FEV1 before education (p-Value 0.941; p>0.05), but there is a significant relationship between the technique of using the inhaler with the results of FEV1 after education (p-Value 0.049; p < 0.05).